Analysis of the Medical Device Maintenance System at Malahayati Islamic Hospital Medan - Rahma, Putri Aulia; Barokah, Wuni; Wardani, Icha Febi; Hasibuan, Nur Cahaya; Hasibuan, Indah Doanita (Ahmar Metastasis Health Journal, 2025)
Ensuring efficient maintenance of medical equipment is crucial to maintaining the quality of hospital services and patient safety. However, many hospitals have difficulty carrying out this maintenance consistently. This study aims to examine the medical device maintenance system at the Malahayati Islamic Hospital in Medan and to assess the extent to which the system complies with the Standard Operating Procedure (SOP). In addition, this study also aims to identify various obstacles that arise during the process of implementing the system maintenance. This study uses a qualitative descriptive approach by conducting in-depth interviews with three main informants, namely the head of the medical support section, electromedical technicians, and members of the Hospital Maintenance Unit (UPRS The results of the study revealed that several maintenance activities had been carried out in accordance with Standard Operating Procedures (SOPs), such as preventive maintenance scheduling, annual calibration, and recording of technical documentation. However, several obstacles were found, including the limited number of qualified personnel (only one technician was available), limited maintenance budget, unavailability of special work space, and SOP coverage that did not yet cover all medical devices. In order for the maintenance system to run more effectively and sustainably, improvements are needed in aspects of human resources, supporting facilities, and more mature budget planning.